2021
DOI: 10.1186/s13014-021-01902-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and treatment-related burden during ocular proton therapy: a prospective trial of 131 patients with uveal melanoma

Abstract: Background Proton beam therapy is a well-established treatment option for patients with uveal melanoma (UM). The treatment procedure, in general, includes placing radiopaque clips to ensure exact eye-positioning during radiotherapy, followed by the delivery of proton irradiation. The short-term burden associated with proton therapy in patients with UM has rarely been addressed. In this prospective study, we investigated the physiological and psychological aspects of proton thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Most of those patients were treated with proton beam therapy. In addition, in a preliminary study, we reported declines in fear of recurrence immediately and 3 months after proton beam therapy, compared to pre‐therapeutic assessments 23 . Apparently, for most patients, anxiety promptly and significantly recedes after completing a primary treatment, and it continues to decline over time 13 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Most of those patients were treated with proton beam therapy. In addition, in a preliminary study, we reported declines in fear of recurrence immediately and 3 months after proton beam therapy, compared to pre‐therapeutic assessments 23 . Apparently, for most patients, anxiety promptly and significantly recedes after completing a primary treatment, and it continues to decline over time 13 …”
Section: Discussionmentioning
confidence: 84%
“…In addition, in a preliminary study, we reported declines in fear of recurrence immediately and 3 months after proton beam therapy, compared to pretherapeutic assessments. 23 Apparently, for most patients, anxiety promptly and significantly recedes after completing a primary treatment, and it continues to decline over time. 13 However, previous studies reported persistently high anxiety over the long term, after primary treatment, in a particular sub-cohort of patients.…”
Section: Anxietymentioning
confidence: 99%
“…In contrast, previous studies consistently reported improvements in anxiety issues for patients with uveal melanoma within the 1st 2 years after a primary treatment, compared to pretreatment assessments [19, 21, 22]. However, another study found that anxiety receded, to a large extent, immediately after PT and remained relatively stable thereafter [23].…”
Section: Discussionmentioning
confidence: 89%
“…Most of the included studies (15), investigated UM [ 5 , 17 , 28 , 30 , 37 , 40 48 ] with three studies on RB [ 16 , 33 , 49 ]. Among the included articles, one [ 49 ] study was carried out in a low- or middle-income country (China) and 16 studies were conducted in high-income countries: the US (9) [ 16 , 17 , 28 , 30 , 33 , 40 42 , 47 ], Germany (4) [ 37 , 43 , 46 , 48 ], Ireland (1) [ 5 ], Israel (1) [ 44 ], and the Netherlands (1) [ 45 ]. In relation to study design, there are ten cohort studies [ 28 , 30 , 33 , 37 , 40 , 41 , 44 46 , 48 ], five cross-sectional studies [ 5 , 16 , 17 , 47 , 49 ], and two longitudinal studies [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analyses showed independent prediction by 6-month depression and decreasing QOL over 6–12 months and 12–24 months. Gollrad et al (2021) [ 46 ] Surgery + Radiotherapy ( n = 131) a) 131 b) 66/65 a) QOL, anxiety b) EORTC QLQ-C30, QLQ-OPT30, GAD-7 Before clip-surgery, between clip-surgery and proton therapy, after proton therapy, and three months after treatment Yes at short-term, no at long-term Global QOL was similar to that in Germany before treatment, and returned to baseline levels three months after treatment. Compared with clip-surgery and three months after treatment, there was no change, but three months after treatment had more eye-specific symptoms than clip-surgery ( P < 0.001).…”
Section: Methodsmentioning
confidence: 99%